Communication Strategy of Bendesa Traditional Leaders In Maintaining Environmental Sustainability Based On Local Wisdom In Penglipuran Village Bali - Sri Desti Purwatiningsih; Sri Ekowati (International Journal of Artificial Intelligence Research, 2022)
The traditional Balinese nuances can be felt strongly in Penglipuran Bali's village, where roofs are decorated with Balinese carvings at the edges. The buildings of the village that are partly still made of compacted clay that is dried and arranged like bricks and Cambodian flower rows along the pathway add to the beauty of the environment. The Penglipuran Village is one of the ancient villages still holding strict customs and traditions. Various forms of ritual activity, as well as methods in the social life of society, are still running. They exist even though globalization continues to threaten and influence them. Local wisdom is one way to maintain environmental sustainability; it is a way that the Penglipuran village community can survive according to environmental conditions, needs, and beliefs that are already rooted and cannot be eliminated. The purpose of the study is to determine the communication strategy of traditional leaders in maintaining the sustainability of life based on local wisdom in the village of Penglipuran Bali, using a qualitative approach in the systematic review to synthesize (summarize) the results of research in a qualitative descriptive manner. This method of synthesizing (summarizing) the result of qualitative research is called